2020
DOI: 10.1038/s41598-020-72301-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating causal relationships between Body Mass Index and risk of atopic dermatitis: a Mendelian randomization analysis

Abstract: Population studies suggest that atopic dermatitis (AD) is associated with an increased risk of obesity, however a causal relationship between these two conditions remains to be established. We therefore use Mendelian randomization (MR) to evaluate whether obesity and AD are causally interlinked. We used summary statistics extracted from genome wide association studies of Body Mass Index (BMI) and AD. MR analysis was performed in both directions to establish the direction of causality between BMI and AD. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
(90 reference statements)
3
12
0
1
Order By: Relevance
“…As a testament to the validity of this study’s findings, a recent publication by Yew et al . using MR analyses yielded similar conclusions 8 …”
Section: Figuresupporting
confidence: 62%
See 1 more Smart Citation
“…As a testament to the validity of this study’s findings, a recent publication by Yew et al . using MR analyses yielded similar conclusions 8 …”
Section: Figuresupporting
confidence: 62%
“…As a testament to the validity of this study's findings, a recent publication by Yew et al using MR analyses yielded similar conclusions. 8 Given that AD often arises in childhood, the authors examined the causality of BMI on AD onset using SNPs associated with childhood obesity and reported a similar causal effect. While the implications on BMI causality on AD risk are intriguing, examining the clinical impact of an intervention on BMI as a means of reducing AD risk would need to be assessed with a clinical trial as this study's findings do not necessarily inform the clinical impact of a weight loss intervention in childhood on the onset of AD in later life.…”
mentioning
confidence: 99%
“…To investigate the causal relationship between AD and obesity, Yew, Y. W et al conducted a Mendelian randomization (MR) analysis using data extracted from genome-wide association studies (GWAS) of Body Mass Index (BMI) and AD (Yew et al, 2020). They found that increase in obesity determined by susceptible genes is associated with increased risk of AD (odds ratio of AD 1.08 [95% CI 1.01 to 1.14; p = 0.015] per unit increase in BMI).…”
Section: 2the Causal Relationship Between Ad and Adipositymentioning
confidence: 99%
“…This is significant as it sets the scope and direction on current and future work to evaluate the observed links between obesity and AD. This finding has recently been published in a peer-reviewed journal [227].…”
Section: Strengths Of Studysupporting
confidence: 57%
“…Beyond a mere chronic skin condition, AD has been reported to be associated with adiposity as well as other co-morbidities in various epidemiological studies. This is further supplemented by recent evidence that genetically determined increase in adiposity is related to an increased risk of AD [227].…”
Section: Overview and Rationalementioning
confidence: 94%